Web-based of Smart Water Quality Monitoring System - TAN, YEE HAN; Hamid Ali, Firkhan Ali (Applied Information Technology And Computer Science, 2025)
The Web-based of Smart Water Quality Monitoring System is a water quality monitoring system specially designed for Bao Lin Yuan Nursery to control the quality of water in the plantation. This water quality monitoring system based on the Internet of Things (IoT) is designed using the TS-300B turbidity sensor and pH sensor for enabling the detection of water turbidity and pH value of the water. The primary objective of this system is to assist the owner in monitoring water quality, safeguarding plants from potential harm due to water impurities. The use of this comprehensive system ensures careful management, thereby reducing the risks of poor water quality. The structured approach is used to develop the system using various IoT devices such as the TS-300B turbidity sensor, pH sensor kit, ultrasonic sensor and Node MCU ESP8266. This system also integrates with ThingSpeak as the database. The waterfall methodology was used to complete the project because it is an iterative, phased approach that emphasizes distinct stages of development. As the result, this system able to provide user-friendly interface for the owner of the nursery to manage their staff, manage the water tank registered and monitoring status of the water tank in their plantation, making it easier to control the water quality.